1993
DOI: 10.1128/cmr.6.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and pathophysiology of bacterial meningitis

Abstract: Bacterial meningitis remains a disease with associated unacceptable morbidity and mortality rates despite the availability of effective bactericidal antimicrobial therapy. Through the use of experimental animal models of infection, a great deal of information has been gleaned concerning the pathogenic and pathophysiologic mechanisms operable in bacterial meningitis. Most cases of bacterial meningitis begin with host acquisition of a new organism by nasopharyngeal colonization followed by systemic invasion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(53 citation statements)
references
References 174 publications
1
52
0
Order By: Relevance
“…Infections caused by encapsulated bacteria such as Neisseria meningitidis, Haemophilus influenzae, and Escherichia coli are a major cause of morbidity and mortality in neonates and infants (1)(2)(3). The capsular polysaccharide is a major virulence factor in these organisms.…”
mentioning
confidence: 99%
“…Infections caused by encapsulated bacteria such as Neisseria meningitidis, Haemophilus influenzae, and Escherichia coli are a major cause of morbidity and mortality in neonates and infants (1)(2)(3). The capsular polysaccharide is a major virulence factor in these organisms.…”
mentioning
confidence: 99%
“…N. meningitidis causes meningitis, which is due to the meningococcal invasion into the human central nervous system, including cerebrospinal fluid (CSF) [36-38]. It has been shown that meningococcal GGT has a physiological function of acquiring cysteine from environmental γ-glutamyl-cysteinyl peptides under cysteine-limited environments such as the CSF [39].…”
Section: Discussionmentioning
confidence: 99%
“…Each of these cytokines in turn can stimulate the production of other inflammatory mediators (eg, interleukin-6, platelet activating factor, interferons, other interleukins), activate and attract leukocytes, and activate the coagulation cascade. The end result is an increased permeability of the blood-brain barrier, thrombosis of vessels and decreased cerebral blood flow, cerebral edema, and increased intracranial pressure; these findings may be exaggerated with certain pneumococcal serotypes, resulting in more severe tissue damage and sequelae [17,21,22]. Pneumococcal meningitis occurs more frequently in children between the ages of 6 and 18 months; it is important to note, however, that in this age group presentation with the classic signs and symptoms of meningitis are least likely until fairly late in the disease course.…”
Section: Pathogenesis and Clinical Findings In Pneumococcal Meningitismentioning
confidence: 99%